Correlation between subfoveal choroidal thickness and optic nerve head changes using optical coherence tomography in cases of primary open-angle glaucoma - Mohamed M.S. Ahmed; Mahmoud A. Kamal; Mahmoud A.E. Hassan; Mahrous H.A.E. Shaheen (Delta Journal of Ophthalmology)
Background There has been increasing interest in investigating the role of the choroid in the pathogenesis of glaucomatous optic neuropathy. While measurement of the choroidal thickness (CT) by spectral domain optical coherence tomography (SD-OCT) would be an attractive add in the diagnosis and monitoring tools in glaucoma, the potential role of CT as a risk factor requires further investigation.